Childhood vaccines and Kawasaki disease, Vaccine Safety Datalink, 1996-2006. Issue 2 (3rd January 2015) - Abrams, Joseph Y.; Weintraub, Eric S.; Baggs, James M.; McCarthy, Natalie L.; Schonberger, Lawrence B.; Lee, Grace M.; Klein, Nicola P.; Belongia, Edward A.; Jackson, Michael L.; Naleway, Allison L.; Nordin, James D.; Hambidge, Simon J.; et al.
Highlights Longitudinal, multi-site study on 1.7 million children for 4.4 million person-years. No evidence for increased rate of Kawasaki disease following vaccination. Observed decreased rate of Kawasaki disease during 42 days after vaccination. Findings provide strong evidence that vaccines are not a cause of Kawasaki disease.